Personal Reputation Management in SMEs in Puebla (AACINI - International Journal of Industrial Engineering, 2024)
"Personal Reputation Management in SMEs in Puebla", written by Ramsés Cabrera Gala, addresses the topic of personal reputation and its impact on customer perceptions in the context of Small and Medium Enterprises in Puebla. With methodological rigor and a friendly reading style, it invites us to analyze the different components of a common concept such as personal reputation, offering a multidimensional and approachable perspective.
Keywords: Personal Reputation; Small and Medium Enterprises; Impact on perceptions